Socialização da leitura: formação do leitor literário no ensino fundamental II - Telma Sales Nogueira da Silva (2021)
This dissertation presents a literary literacy proposal that aims to stimulate the students' enjoyment of reading literature, through strategies that democratize and socialize it, integrating the School Library and its collection. Reflecting on the practice of literary teaching, we realize that students, especially in Elementary, have little or no experience in reading literary books and show little interest in this reading. The reading assignments proposed by most elementary schools are often aimed only at determining a work to be read to develop specific activities after reading. This practice does not favor the enjoyment of reading literature, besides not considering the student's interests, and not aiming at the reading socialization. The project would be carried out in a public school in Sabará/MG, whose library has a very extensive collection of literary books, however, little explored. After being affected by the Covid-19 world pandemic, it is presented as a proposition, which can be applied later and in other school institutions. In rethinking the practice of literary teaching, the present proposition reflects on the following questions: does the teacher's mediation, aiming to stimulate in the student autonomy in the choice of literary books, contribute to the literary reader education? Does the use of a digital tool collaborate with the practice of socializing literary reading at school? In view of these reflections, it is observed that with the teacher's mediation in the students' choice of books, the activities proposed before, during and after reading each work, and their socialization, significant literary reading experiences are favored in the students, a fact that contributes to stimulating the enjoyment of reading and enables the formation of a community of readers, which contributes to the experience of literature inside and beyond the school. The use of a digital technology support, the QR Code (Quick Response Code), used to make available the work developed by students through literary readings, encourages the socialization of these readings, as well as the social network Instagram, where photos of the activities developed by students throughout the project will be posted. The practice of this project is based on the Literary Literacy theory proposed by Cosson (2007). The theoretical framework is based in Freire (1989), Solé (1998), Zilberman and Silva (2008), Candido (1995), Cafiero (2005), Cosson (2019), Todorov (2009), Colomer (2007), Soares (2006), Coscarelli and Ribeiro (2014).